New Approach to Estimate Furan Contents in Transformer Oil Using Spectroscopic Analysis - Das, Narottam; Abu-Siada, Ahmed; Islam, Syed (Institut Teknologi Sepuluh Nopember (ITS), 2012)
The presence of furan derivatives in aged-transformer oil has been one of the key indicators for solid dielectric deterioration. Identification and quantification of furan derivatives are currently performed using high performance liquid chromatography (HPLC) or gas chromatography-mass spectrometry (GC/MS) based on ASTM D5837 standard. Although these techniques are well developed, they call for an expert personal to conduct the test and to analyse its results. Moreover, the test is relatively expensive and the analysis of oil sample may take days as most utilities sending transformer oil samples to external laboratories to be tested. This paper introduces a novel approach to determine the furan concentration within power transformer dielectric oil through ultraviolet to visible (UV-Vis) spectroscopic analysis for oil samples. Furan concentration in transformer oil would determine the absorption intensity in UV-Vis spectral range and hence the correlation between furan concentration and spectral response of transformer oil can be identified. Experimental results show that the new technique is reliable, economic and easy to be implemented on site to identify the furan concentration level in transformer oil instantly.